USP25 Ameliorates Pathological Cardiac Hypertrophy by Stabilizing SERCA2a in Cardiomyocytes. Issue 4 (1st February 2023) - Ye, Bozhi; Zhou, Hao; Chen, Yanghao; Luo, Wu; Lin, Wante; Zhao, Ying; Han, Jibo; Han, Xue; Huang, Weijian; Wu, Gaojun; Wang, Xu; Liang, Guang
Abstract : Background: Pathological cardiac hypertrophy can lead to heart failure and is one of the leading causes of death globally. Understanding the molecular mechanism of pathological cardiac hypertrophy will contribute to the treatment of heart failure. DUBs (deubiquitinating enzymes) are essential to cardiac pathophysiology by precisely controlling protein function, localization, and degradation. This study set out to investigate the role and molecular mechanism of a DUB, USP25 (ubiquitin-specific peptidase 25), in pathological cardiac hypertrophy. Methods: The role of USP25 in myocardial hypertrophy was evaluated in murine cardiomyocytes in response to Ang II (angiotensin II) and transverse aortic constriction stimulation and in hypertrophic myocardium tissues of heart failure patients. Liquid chromotography with mass spectrometry/mass spectrometry analysis combined with Co-IP was used to identify SERCA2a (sarcoplasmic/endoplasmic reticulum Ca2+-ATPase 2A), an antihypertrophy protein, as an interacting protein of USP25. To clarify the molecular mechanism of USP25 in the regulation of SERCA2a, we constructed a series of mutant plasmids of USP25. In addition, we overexpressed USP25 and SERCA2a in the heart with adenoassociated virus serotype 9 vectors to validate the biological function of USP25 and SERCA2a interaction. Results: We revealed increased protein level of USP25 in murine cardiomyocytes subject to Ang II and transverse aortic constriction stimulation and in hypertrophic myocardium tissues of patients with heart failure. USP25 deficiency aggravated cardiac hypertrophy and cardiac dysfunction under Ang II and transverse aortic constriction treatment. Mechanistically, USP25 bound to SERCA2a directly via its USP (ubiquitin-specific protease) domain and cysteine at position 178 of USP25 exerts deubiquitination to maintain the stability of the SERCA2a protein by removing the K48 ubiquitin chain and preventing proteasomal pathway degradation, thereby maintaining calcium handling in cardiomyocytes. Moreover, restoration of USP25 expression via adenoassociated virus serotype 9 vectors in USP25 −/− mice attenuated Ang II-induced cardiac hypertrophy and cardiac dysfunction, whereas myocardial overexpression of SERCA2a could mimic the effect of USP25. Conclusions: We confirmed that USP25 inhibited cardiac hypertrophy by deubiquitinating and stabilizing SERCA2a.